Dapagliflozin in the Landscape of Type 2 Diabetes Management (Indian Journal Of Clinical Practice, 2022)
As per current statistics, India accounts for more than 74 million individuals living with diabetes. Many of these individualshave associated cardiovascular disease (CVD) and chronic kidney disease (CKD) comorbidities. Optimal glycemic managementis important because uncontrolled glycemia may accelerate the macrovascular and microvascular complications, furtheraggravating the comorbid conditions. Metformin is used as the first-line therapy in most persons. However, there are somewho do not tolerate metformin, are unable to achieve required glycemic targets or require greater efforts for cardiovascular(CV) risk reduction. These patients require an alternative hypoglycemic agent to be used as either monotherapy or ascombination treatment with metformin, respectively. Sodium-glucose cotransporter-2 (SGLT2) inhibitors are one such novelclass of drugs that can be used as either monotherapy or as part of two drug (dual) or three drug (triple) combinations withother oral hypoglycemic agents or insulin. Dapagliflozin is a promising option for managing type 2 diabetes with CV andrenal benefits, weight and blood pressure reducing properties. A low risk of hypoglycemia and drug-drug interactions are theadded advantages. In this article, the authors have reviewed the existing clinical evidences on dapagliflozin and highlightedits place in the diabetes management landscape.